Polymer Nanocomposites for Advanced Engineering and Military Applications - Ramdani, Noureddine, 1986-, editor (Hershey, PA : IGI Global, 2019)
"This book provides the latest developments and research findings in the area of polymer nanocomposites. It also examines the recent advances in the fabrication methods, properties, and applications of various nano-fillers reinforced-polymeric matrix nanomaterials".